High‐risk HPV positivity is a long‐term risk factor for recurrence after cervical excision procedure in women living with HIV. Issue 3 (10th June 2021) - Agarossi, Alberto; Delli Carpini, Giovanni; Sopracordevole, Francesco; Serri, Matteo; Giannella, Luca; Gardella, Barbara; Maestri, Marta; Del Fabro, Anna; Sansone, Matilde; Fallani, Maria Grazia; Pieralli, Annalisa; Fasolo, Maria Michela; et al.
Abstract: Objective: To evaluate the risk factors for recurrence of high‐grade disease after cervical excision in women living with HIV (WLWH), with a specific interest in the role of high‐risk (HR‐) HPV positivity. Methods: Multicentric retrospective study conducted on WLWH who underwent cervical excision between January 1987 and June 2017 in six Italian institutions. The rate of high‐grade recurrence was determined. Risk factors for recurrence and HR‐HPV positivity were determined with the Log‐rank test and Cox proportional hazards regression models. Results: A total of 271 WLWH were included in the final analysis. A high‐grade recurrence was found in 58 (21.4%) patients. Age 41 years or more at inclusion and HR‐HPV positivity during follow up were independently associated with a higher risk of disease recurrence with relative risks of 4.15 (95% confidence interval [CI] 2.01–8.58, P < 0.001) and 5.18 (95% CI 2.12–12.67, P < 0.01), respectively. Age 41 years or more (relative risk 1.75, 95% CI 1.01–3.04, P = 0.047) resulted as a risk factor for HR‐HPV positivity during follow up. Conclusion: HR‐HPV positivity is a risk factor for recurrence after cervical excision in WLWH. Women older than 41 years may benefit from a long‐term yearly follow up. Future studies regarding HPV vaccination after treatment in WLWH may be useful, considering the protective role of the higher probability of HPV negativity in vaccinated women. Synopsis: High‐risk‐HPV positivity during long‐term follow up is a risk factor for high‐grade disease recurrence after cervical excisional treatment in women living with HIV.